brother of rhomboid, a rhomboid-related gene expressed during early Drosophila oogenesis, promotes EGF-R/MAPK signaling. - Guichard, A.; Roark, M.; Ronshaugen, M.; Bier, E. (Developmental Biology, 2000)
The Drosophila rhomboid (rho) gene participates in localized activation of EGF-receptor signaling in various developmental settings. The Rhomboid protein has been proposed to promote presentation and/or processing of the membrane-bound Spitz (mSpi) EGF-related ligand to generate an active diffusible form of the ligand. Here, we report on a new rhomboid-related gene identified by sequence similarity searching that we have named brother of rhomboid (brho). In contrast to rho, which is expressed in complex patterns during many stages of development, brho appears to be expressed only during oogenesis. brho transcripts are present in early oocytes and abut posterior follicle cells which exhibit high levels of MAPK activation. brho, like rho, collaborates with Star to promote signaling through the EGF-R/MAPK pathway, and genetic evidence indicates that Brho can activate both the mSpi and the Grk precursor EGF ligands in the wing. We propose that endogenous brho may activate the oocyte-specific Gurken ligand and thereby participate in defining posterior cell fates in the early follicular epithelium.